RESIDUAL STEREOTOMOGRAPHIC INVERSION - Neckludov D.; Baina R.; Landa E. (My University, 2006)
Depth migration requires highly accurate knowledge of the subsurface velocity field. Different traveltime tomographic methods are used for this purpose. Stereotomography is a tomographic method that uses local dip estimates in addition to traveltimes for velocity model estimation. We present a new methodology for velocity model updating. It combines poststack stereotomography and residual moveout velocity inversion. The former is used for initial model construction and the latter for updating the velocity model. Residual inversion is a kind of stereotomographic inversion applied to common reflection point (CRP) gathers after model-based moveout correction. Velocity analysis can be made more efficient by preselecting the traces that contribute to a series of CRP gathers and using only these traces for inversion. The algorithm is defined in a two-step procedure. First, ray tracing from the reflection point for nonzero reflection offsets defines the source and receiver locations of the data traces in the CRS gather. Then these traces are moveout corrected according to the calculated traveltimes and residual moveout is estimated. The interval velocity model is updated by fitting the velocity that minimizes estimated residuals. Application of the proposed technique demonstrates its robustness and reliability for fast and automatic velocity model estimation. © 2006 Society of Exploration Geophysicists.
Keywords: GEOPHYSICAL TECHNIQUES; RAY TRACING; SEISMIC WAVES; TOMOGRAPHY